2015
DOI: 10.1021/acs.langmuir.5b00993
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Threadlike Micelles and DNA-Tethered Nanoparticles: A Structural Study of PEGylated Cationic Liposome–DNA Assemblies

Abstract: The self-assembly of oppositely charged biomacromolecules has been extensively studied due to its pertinence in the design of functional nanomaterials. Using cryo electronic microscopy (cryo-EM), optical light scattering and fluorescence microscopy, we investigated the structure and phase behavior of PEGylated (PEG: poly(ethylene-glycol)) cationic liposome–DNA nanoparticles (CL–DNA NPs) as a function of DNA length, topology (linear and circular) and ρchg (the molar charge ratio of cationic lipid to anionic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 60 publications
5
44
0
Order By: Relevance
“…While Cryo-TEM studies are consistent with the DLS results, they further reveal (figure 3, bottom) differences in the detailed structure and morphology of PEGylated CL-DNA NPs that depend on DNA length and shape [40]. In contrast with polydisperse salmon sperm DNA, NPs formed with λ-DNA or pGL3 can also exhibit hollow cores in addition to the lamellar morphology from core to surface.…”
Section: Surface Functionalized Cl-dna Complexes: Pegylated Cl-dna Nasupporting
confidence: 77%
See 1 more Smart Citation
“…While Cryo-TEM studies are consistent with the DLS results, they further reveal (figure 3, bottom) differences in the detailed structure and morphology of PEGylated CL-DNA NPs that depend on DNA length and shape [40]. In contrast with polydisperse salmon sperm DNA, NPs formed with λ-DNA or pGL3 can also exhibit hollow cores in addition to the lamellar morphology from core to surface.…”
Section: Surface Functionalized Cl-dna Complexes: Pegylated Cl-dna Nasupporting
confidence: 77%
“…Complexes which contain sufficient PEG-lipids (such that the PEG chains transition from the mushroom to the brush conformation) sterically stabilize CL-DNA complexes against flocculation caused by van der Waals attractions [55][56][57]. Experiments have shown that PEGylated complexes resist aggregation even after extensive centrifugation [40]. Thus, the use of a PEG-lipid improves colloidal stability, and as experiments show PEGylation leads to the spontaneous formation of equilibrium nanoparticles (NPs).…”
Section: Surface Functionalized Cl-dna Complexes: Pegylated Cl-dna Namentioning
confidence: 99%
“…A recent cryo-EM study has found that the DNA length and topology can also influence the average number of layers found in each particle (38). NPs formed with long, linear DNA (48 kbps, lambda DNA) or circular plasmid (2 kbps, pDNA) results in more layers than NPs formed with polydisperse, linear DNA (2 kbps, salmon DNA).…”
Section: Introductionmentioning
confidence: 99%
“…Dual fluorescent labeling permits discrimination between CL–DNA NPs and cationic liposomes lacking DNA (which coexist at equilibrium, see Fig. 4B) (24,38). Furthermore, dual-labeled CL–DNA complexes allow direct visualization of vector-cargo disassociation (39,45).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation